Interaction of phospholipase enzymes with autophagic processes; importance for cell signaling and therapeutics - Joyce Nirmala, Manoj G Tyagi, Kapil D Sagar, K Arumugasamy, Divya V (Journal of Biomedical and Pharmaceutical Research, 2017)
Phospholipases are inherently involved in signalling mechanisms of various neurotransmitters and hormones. Cytosolic phospholipase (cPLA2) initiates pro-inflammatory lipid mediator pathways which play a critical role in host defense and in inflammation. The crosstalk between the two pathways remains unclear. In this article, the important roles of the three phospholipases i.e PLC, PLD and PLA2 are investigated in the autophagic processes and their link to intracellular kinetics of signalling molecules. While autophagy delivers cytoplasmic constituents to autophagosomes and is involved in innate and adaptive immunity. The cPLA2 and its metabolite lipid mediators have been shown to induce autophagy in the macrophage cell line and in primary monocytes. Cysteinyl leukotrienes D4 and E4 and PGD2 also induced these effects. The autophagy is independent of changes in mTOR or autophagic flux. cPLA2 and lipid mediator-induced autophagy is ATG5 dependent. These data suggest that lipid mediators seem to play a role in the regulation of autophagy, demonstrating a connection between the two seemingly separate innate immune responses, induction of autophagy and lipid mediator generation. Keywords: PLA2, PLD, PLC, autophagy, lipid, cell, drug